Deep‐Eutectic‐Solvent‐Based Self‐Healing Polymer Electrolyte for Safe and Long‐Life Lithium‐Metal Batteries - Jaumaux, Pauline; Liu, Qi; Zhou, Dong; Xu, Xiaofu; Wang, Tianyi; Wang, Yizhou; Kang, Feiyu; Li, Baohua; Wang, Guoxiu (Angewandte Chemie International Edition, 2020)
The deployment of high‐energy‐density lithium‐metal batteries has been greatly impeded by Li dendrite growth and safety concerns originating from flammable liquid electrolytes. Herein, we report a stable quasi‐solid‐state Li metal battery with a deep eutectic solvent (DES)‐based self‐healing polymer (DSP) electrolyte. This electrolyte was fabricated in a facile manner by in situ copolymerization of 2‐(3‐(6‐methyl‐4‐oxo‐1,4‐dihydropyrimidin‐2‐yl)ureido)ethyl methacrylate (UPyMA) and pentaerythritol tetraacrylate (PETEA) monomers in a DES‐based electrolyte containing fluoroethylene carbonate (FEC) as an additive. The well‐designed DSP electrolyte simultaneously possesses non‐flammability, high ionic conductivity and electrochemical stability, and dendrite‐free Li plating. When applied in Li metal batteries with a LiMn2O4 cathode, the DSP electrolyte effectively suppressed manganese dissolution from the cathode and enabled high‐capacity and a long lifespan at room and elevated temperatures. Safety first: A deep eutectic solvent (DES)‐based self‐healing polymer electrolyte with high safety for lithium metal batteries was fabricated in situ by integrating an UPyMA‐PETEA copolymer matrix with a nonflammable DES+FEC electrolyte (see picture; FEC=fluoroethylene carbonate). The multifunctional electrolyte showed high ionic conductivity, stable interfacial characteristics without dendrite formation, and stable cycling in lithium metal batteries.